Competition law and the World Trade Organization : the limits of multilateralism - Kennedy, Kevin C. (Sweet & Maxwell LondonGB, 2001)
Analyzes the WTO's unfinished agenda and critiques the WTO's proposed new agenda in the area of competitive policy.